2015
DOI: 10.5530/jcdr.2015.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Iron Status and Cardiovascular Risk Factors in Patients with Coronary Artery Disease

Abstract: Background: Iron is an essential trace element. It has a pivotal role in maintaining various cellular functions and enzyme reactions; whereas, iron overload has been known as a risk factor in progression of atherosclerosis. Objectives: The aim of this study was to investigate the role of the serum iron, serum ferritin and total iron binding capacity (TIBC) in the causation of coronary artery disease (CAD) and their relationship with other risk factors of CAD. Material and Methods: The study group consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…This study was consistent with that by Das De et al, A 2015 study showed a significant association between markers of iron status and IHD. Furthermore, this study was consistent with that reported by Suuny Chopra et al, A 2015 study confirmed that an IHD patient experienced a significant increase in his S. iron and ferritin and a significant decrease in his TIBC [16]. Furthermore, the results showed that the average PT was in males (13.3 s) and females (13.5 s).…”
Section: Discussionsupporting
confidence: 91%
“…This study was consistent with that by Das De et al, A 2015 study showed a significant association between markers of iron status and IHD. Furthermore, this study was consistent with that reported by Suuny Chopra et al, A 2015 study confirmed that an IHD patient experienced a significant increase in his S. iron and ferritin and a significant decrease in his TIBC [16]. Furthermore, the results showed that the average PT was in males (13.3 s) and females (13.5 s).…”
Section: Discussionsupporting
confidence: 91%